Errors in Interpretation of Magnetic Resonance Imaging for Thymic Lesions. Issue 6 (November 2019) - Hammer, Mark M.; Barile, Maria; Bryson, Wesley; Bhalla, Sanjeev; Raptis, Constantine A.
Abstract : Purpose: The objectives of this study were to evaluate the magnetic resonance imaging (MRI) features of thymic lesions and to review those features that may result in diagnostic uncertainty or error. Materials and Methods: This multicenter retrospective study included patients with pathologically proven thymic epithelial neoplasms (TEN) and thymic cysts who underwent preoperative MRI. Clinical reports were evaluated for the radiologist's first-choice diagnosis, if not already known before the MRI. MR images were reviewed by thoracic radiologists to identify cystic components on T2-weighted imaging (T2WI) as well as the presence of enhancement on postcontrast series. Results: Through a search of electronic medical records of 3 tertiary academic medical centers, we identified 41 TEN and 13 cysts. Of 35 evaluable clinical reports, 9 (26%) gave an incorrect diagnosis. Of these, 5 cases were misdiagnosed related to contrast enhancement, and 3 cases of cysts were misdiagnosed because of lack of fluid signal on T2WI. Upon rereview of images, of the 41 TENs, 4 (10%) did not show qualitative enhancement on the first postcontrast phase (although all enhanced eventually), and 4 cysts (31%) did not show fluid signal on T2WI. In addition, 4 cases of cysts (31%) showed mural or septal enhancement. Conclusions: Although atypical or misleading imaging features are uncommon in TEN and thymic cysts, they do occur and may lead to diagnostic error. We suggest that lesions with a T2 signal less than simple fluid and without enhancement on postcontrast images undergo follow-up imaging to confirm a benign diagnosis.